Cockpit Visualization of Curved Approaches based on GBAS. Issue 4 (29th November 2013) - Geister, Robert; Kapol, Tatjana
ABSTRACT The demand for fuel efficient flight paths which include shorter routes and routes adapted to the prevailing terrain as well as the aim to reduce the perceived noise on the ground in the terminal maneuvering area of airports lead to the development of curved approach procedures. In this paper, curved precision approach procedures solely based on a single receiver are evaluated and different means of presenting deviation information to the pilot are analyzed. The Terminal Area Path (TAP) functionality of a Ground Based Augmentation System (GBAS) is used as a technical enabler for curved approaches. Based on that, a simulation and flight trial assessment regarding the technical feasibility and the manual flyability of a descending curved approach was carried out. In addition, multiple display layouts and guidance cues were tested during the flight trials. Copyright © 2013 Institute of Navigation.